ANALISIS FAKTOR YANG MEMPENGARUHI PRICE TO BOOK VALUE SAHAM (PADA BANK YANG TERDAFTAR DI BEI PERIODE 2005-2008) - Mudrika Alamsyah Hasan (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
he purpose of this research is to exam the effect of factors consists of CapitalAdequacy Ratio, Non Performing Loan, Loan to Deposit Ratio, Return on Equity, NetInterest Margin and Operational Expenses per Operational Revenues to Price ofBook Value of Stock both stimulatingly and partially. And the other purpose of thisresearch is to indicate dependence variables that have dominant influence to Priceof Book Value. The populations of this research are banking firms listed in IndonesiaStock Exchange during period 2005 to 2008. The samples of this research choiceusing purposive sampling method and resulting 18 banking firms. Statistic methodis using multiple regression analysis. The conclusion of the research is: stimulatinglyCAR, NPL, LDR. ROE, NIM and BOPO variables are influencing to the PBV of stocksignificantly. It shown by F value is 14.121 with significant value 0,000. So, all of sixindependent variables could be used for the analysis price of book value of stock.Partially, only 4 (four) from 6(six) variables that have significant influence to PBV ofstock namely CAR, ROE, NIM and BOPO which is shown that significant level less2than 5%. Adjusted R is 0.526, it means that 52,6% of PBV changes can beexplained by Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan toDeposit Ratio (LDR), Return on Equity (ROE), Net Interest Margin (NIM) andOperational Expenses per Operational Revenues (BOPO), and 47,4% are remainthat explained by other reasons.